2016
DOI: 10.1001/jamaoncol.2015.4333
|View full text |Cite
|
Sign up to set email alerts
|

Neurotoxic Effects of Anthracycline- vs Nonanthracycline-Based Chemotherapy on Cognition in Breast Cancer Survivors

Abstract: IMPORTANCE Chemotherapy exposure is a known risk factor for cancer-related cognitive impairments. Anthracycline-based regimens are commonly used chemotherapies that have been shown to be associated with cognitive impairment and brain changes in clinical studies. OBJECTIVE To directly compare the effects of anthracycline and nonanthracycline regimens on cognitive status and functional brain connectivity. DESIGN, SETTING, AND PARTICIPANTS In this observational study, we retrospectively examined cognitive and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
121
4
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 129 publications
(140 citation statements)
references
References 73 publications
9
121
4
1
Order By: Relevance
“…It is possible that these factors are most important in determining the overall impact of cognitive impairment on QOL as well as how others, for example, caregivers, view the patient's cognitive function. Whereas research demonstrates that anthracycline agents are more inflammatory 27,28 and neurotoxic 18 than nonanthracyclines, our study shows patients being treated with either regimen experience CRCI similarly. In addition, those who received hormone therapies and/or radiation therapy after chemotherapy did not experience CRCI statistically differently from those who did not receive these modalities.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…It is possible that these factors are most important in determining the overall impact of cognitive impairment on QOL as well as how others, for example, caregivers, view the patient's cognitive function. Whereas research demonstrates that anthracycline agents are more inflammatory 27,28 and neurotoxic 18 than nonanthracyclines, our study shows patients being treated with either regimen experience CRCI similarly. In addition, those who received hormone therapies and/or radiation therapy after chemotherapy did not experience CRCI statistically differently from those who did not receive these modalities.…”
Section: Discussioncontrasting
confidence: 72%
“…We also hypothesized that patients who received anthracyclines-thought to be cardiotoxic and neurotoxic [15][16][17][18] -would lead to more cognitive complaints than in those who received nonanthracycline regimens.…”
Section: Introductionmentioning
confidence: 99%
“…Current data suggests that especially anthracycline-based chemotherapeuticregimes have a negative effect on verbal memory performance and left precuneus connectivity [58]. Furthermore, the exact influence of hormone therapies is still unknown and therefore their exact role remains to be determined [3].…”
Section: Discussionmentioning
confidence: 99%
“…Lekovich et al 21 statistically analyzed the incidence of depression in 95 BC patients within 1-6 months after chemotherapy, and reported it to be up to 67%. Recently, certain studies have found that depression in BC patients was not temporary, and some patients have even exhibited high levels of depressive symptoms after the completion of treatment [22][23][24] .…”
Section: Tablementioning
confidence: 99%